DECODING THE RETROPERITONEAL MYSTERY: A CASE OF FOLLICULAR LYMPHOMA - RAVITEJA NALABOTHULA; TARUGUVANDLA SANDHYA RANI; BUDUMURI VENKATA SIVA KARTHIK; KEERTHI REDDY KARRA (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Retroperitoneal masses are rare and often difficult to diagnose due to similarities between benign and malignant conditions. Follicular lymphoma (FL), a common indolent subtype of non-Hodgkin lymphoma, can present atypically, complicating early identification. We report a 60-year-old male with abdominal distension, weight loss, and breathlessness. Imaging revealed a large retroperitoneal mass encasing major vessels and associated lymphadenopathy. Biopsy of an enlarged inguinal lymph node confirmed FL through characteristic immunohistochemical markers. The patient was treated with six cycles of R-CHOP chemotherapy, resulting in complete remission. This case highlights the importance of histopathological evaluation in differentiating FL from other retroperitoneal pathologies like retroperitoneal fibrosis. Early and accurate diagnosis enables timely initiation of appropriate therapy, improving patient outcomes. Clinicians should consider FL in the differential diagnosis of retroperitoneal masses with atypical clinical presentations.